Monty Python live (mostly) [videorecording (DVD)] : one down, five to go - Idle, Eric ([Publisher not identified], 2014)
Monty Python are flying again for a final reunion, well, sort of. This hugely anticipated live show took place on June 20th 2014 at the O2 Arena in London. At a combined age of just 357, John Cleese, Terry Gilliam, Eric Idle, Terry Jones and Michael Palin once again take to the stage and perform some Monty Python's greatest hits with modern, topical, Pythonesque twists.